PERBEDAAN SELF-REGULATED LEARNING ANTARA MAHASISWA LAKI-LAKI DAN PEREMPUAN DI PERANTAUAN - Panggah Fahiyan Ristomoyo; Arthur Huwae (Bajang Institute, 2026)
The problems faced by students living away from home are often closely related to academic issues. When self-regulation strategies are not optimal, it can damage the quality of their learning at university. This study aims to determine the differences in self-regulated learning (SRL) between male and female students living away from home. The method used is a comparative study involving 110 first-year students (55 male and 55 female) using accidental sampling. The measurement uses the Self-Regulated Learning Scale (α = 0.859). The results showed a difference in SRL between male and female overseas students (t = 3.984; p = 0.000). These results indicate that male and female students have different abilities to regulate themselves in learning while studying abroad